PENGARUH GOOD CORPORATE GOVERNANCE, KEPEMILIKAN INSTITUSIONAL DAN LEVERAGE TERHADAP PROFITABILITAS PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2016 - Radlia Juniyafie, 16.05.62.0011; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2018)
This research aims to analyze and test the effect of good corporate governance, institutional ownership and leverage leverage on profitability banking companies. This research used banking companies as population that listed in the Indonesia Stock Exchange for the period of 2014-2016.The sample of this study was obtained by purposive sampling methode.This research used 115 banking companies as samples. The type of data used secondary data. This research used multiple regression methode of analysis and the data’s tabulation was processed by software SPSS 22.0 for windows.The results showed that Independence of commissioners, Institutional ownership and Leverage is postive significantly effect on the ROA. Board of directors and audit committee is not affect on the ROA. Keywords: good corporate governance, independent commissionaire,board of director, audit committee, institusional ownership, profitability, leverage, debt to equity ratio, ROA